Perception of special education needs teachers towards in-service training programmes for special education in Sarawak - Gumbang, Rick Hanson (2001)
This study focuses on the perception of Special Education Needs towards In-Service Training for special education in Sarawak. The specific purpose of this study is to examine how the selected demographic factors, organizational factors, trainer factors and trainee factors have influenced the effectiveness of in-service training programmes for special educational needs.